45.8k views
2 votes
2x^2(-5x^2-4)+4x^4 in simplist form, plz help

User Evaneus
by
6.1k points

2 Answers

3 votes

Answer:

-2x^2(3x^2 + 4).

Explanation:

2x^2(-5x^2 - 4) + 4x^4

Distribute the 2x^2 over the parentheses:

= -10x^4 - 8x^2 + 4x^4

= - 6x^4 - 8x^2

= -2x^2(3x^2 + 4).

User Libni
by
5.7k points
5 votes

Answer:

-6x^4-8x^2 or -2x^2(3x^2+4)

Explanation:

Given expression is:


2x^2(-5x^2-4)+4x^4

In order to write the expression in simplest form we have to multiply the terms which needs to be multiplied.

So,


= -10x^4-8x^2+4x^4

Combining alike terms


= -10x^4+4x^4-8x^2\\=-6x^4-8x^2\\

Can also be written as:


= -2x^2(3x^2+4)

User Chris Ciszak
by
6.7k points